Close detection robotic platform for Search And Rescue missions based on Bluetooth Low Energy - Cantizani-Estepa, Juan; Bravo-Arrabal, Juan; Fernández-Lozano, Juan Jesús; Fortes-Rodríguez, Sergio; Barco-Moreno, Raquel; García-Cerezo, Alfonso José (My University, 2022)
Improvements in telecommunications and digitalization directly improve the efficacy of a wide variety of processes. Recently, detection systems have received considerable attention because of the importance of tracking infected people contacts during SARS-CoV-2 pandemic. Such implementations can be useful in the task of finding potential victims in the context of emergency response, especially in situations where GPS is not available or inspection by imaging is not practical. Radio signals come into play, and specifically from devices that transmit periodically and with low power consumption. With the rise of Internet of Things over the last years, the number of wearable devices that support BLE, such as smartbands, smartwatches or smartphones, has been increasing constantly, as well as the number of users that carry them. Those devices can provide considerable assistance in locating injured or unconscious people. This work presents a system for detecting victims by means of a terrestrial search and rescue (SAR) robot. A real implementation of a close detection robotic platform based on BLE for SAR interventions is laid out. To estimate the distance between a robotic agent and potential victims within an experimental area, a Log-distance path loss model is presented. The proposed scheme has been tested in realistic scenarios during SAR exercises.
Keywords: Ayuda en las catástrofes; Robots autónomos; Bluetooth Low Energy; Search and Rescue robot; Emergency scenarios